Common ownership does not have anti-competitive effects in the airline industry - Patrick Dennis; Kristopher Gerardi; Carola Schenone (Federal Reserve Bank of Atlanta, 2019)
Institutional investors often own significant equity in firms that compete in the same product market. These "common owners" may have an incentive to coordinate the actions of firms that would otherwise be competing rivals, leading to anti-competitive pricing. This paper uses data on airline ticket prices to test whether common owners induce anti-competitive pricing behavior. We find little evidence to support such a hypothesis, and show that the positive relationship between average ticket prices and a commonly used measure of common ownership previously documented in the literature is generated by the endogenous market share component, rather than the ownership component, of the measure.
Keywords: G33; G34; G38; L41; L11; 330; common ownership; airline prices; institutional ownership; competition